Camphor sulfonic acid incorporation in SnO2/polyaniline nanocomposites for improved thermoelectric energy conversion. Issue 5 (2nd February 2022) - Debnath, Ajit; Das, Jayanta; Deb, Krishna; Bhowmik, Kartick L.; Saha, Biswajit
Abstract : To modulate carrier transport and hence thermoelectric properties, a facile approach has been undertaken by incorporating tin dioxide (SnO2 ) in polyaniline (PANI) and subsequent treatment with camphor sulfonic acid (CSA). Abstract : To modulate carrier transport and hence thermoelectric properties, a facile approach has been undertaken by incorporating tin dioxide (SnO2 ) in polyaniline (PANI) and subsequent treatment with camphor sulfonic acid (CSA). The results of this study show a simultaneous increase in electrical conductivity and Seebeck coefficient after the incorporation of SnO2 with PANI, which can be attributed to the formation of a highly ordered molecular arrangement with high crystallinity, reduced π–π conjugation defects as well as modification of the hopping free path and hopping activation energy in the composite. Additional improvements have been achieved by CSA treatment of the composite, which significantly increases the effective number of carriers, introduces the delocalization effect, and leads to polaron or bipolaron formation in the composite. The highest power factor of 31.85 μW m −1 K −2 was found at 100 °C for the CSA–SnO2 /PANI nanocomposite, which is about 589 times and 2.89 times higher than those of pure PANI and SnO2 incorporated PANI, respectively. A superior thermoelectric material with an outstanding power factor has thus been produced with a cost-effective and simple method unfolding the potential of such composites for application in thermoelectric generators operative at the low-temperature differences.